Sugarcane straw biochar and cow bonechar: physical-chemical characterization and interference on the behavior of metribuzin in soil and water - Mielke, Kamila Cabral (2023)
The pyrolysis temperature in biochar production and the application rate in soil can influence the sorption, desorption, and degradation of herbicides, as well as soil fertility. The objective of the study was to investigate the effect of soil amendment with different pyrolysis temperature-produced sugarcane straw biochar application rates on the behavior of metribuzin and soil fertility. A second objective was the production of a cellulose acetate film with cow bonechar as a viable alternative for metribuzin removal from water. The treatments for the sorption-desorption and degradation studies of metribuzin consisted of three pyrolysis temperatures (BC350 ºC, BC550 ºC, and BC750 °C) and seven application rates (0, 0.1, 0.5, 1, 1.5, 5, and 10 % w/w). The treatments for the metribuzin removal from water study consisted of 2 and 3 g of bonechar fixed in the cellulose acetate film, pure powdered bonechar (2 g), and a control (without bonechar addition). Metribuzin quantification in soil and water was performed using High Performance Liquid Chromatography (HPLC). The amended soil with different application rates showed a reduction in H + Al and an increase in pH, OC, P, K, Ca, Mg, Fe, Mn, CEC, and BS. Metribuzin sorption and desorption coefficient (Kf) were 1.42 and 0.78 mg(1−1/n) L1/n Kg-1, respectively, for the unamended soil. Biochar application rates <1 % sorbed ~23 % and desorbed ~15 % of metribuzin, similar to the unamended soil, for all pyrolysis temperatures. Amended soil with a 10 % application rate of BC350 ºC, 550 ºC, and 750 ºC sorbed 63.8 %, 75.5 %, and 89.4 % and desorbed 8.3 %, 5.8 %, and 3.7 % of metribuzin, respectively. The values of degradation half-life time, DT50 and DT90, for metribuzin in unamended soil were 7.37 and 24.94 days, respectively. The soil amended with 10% of BC350 ºC increased metribuzin DT50 from 7.35 to 17.32 days and DT90 from 24.41 to 57.26 days compared to the unamended soil. The lower application rates (0.1 to 1.5 %) of BC550 ºC and BC750 ºC decreased metribuzin DT50 to ~4.05 and ~5.41 days, respectively. The amended soil with BC350 ºC at high application rates (5 and 10 %) provided high microbial respiration rate (C-CO2), low carbon fixation of microbial biomass (MBC) and high metabolic rate (qCO2). The addition of 2 and 3 g of bonechar fixed in the cellulose acetate film sorbed 40 % and 60 %, respectively, of metribuzin at lower concentrations (0.25, 0.33, and 0.5 mg L-1). At higher concentrations of 1.0 and 2.0 mg L -1, sorption was 16% and 50% of metribuzin for the addition of 2 and 3 g of bonechar fixed in the cellulose acetate film, respectively. High pyrolysis temperature and application rates of sugarcane straw biochar demonstrate the ability to immobilize metribuzin, improve soil fertility, and increase metribuzin degradation in soil, which can influence weed control effectiveness. The acetate film with bonechar was efficient in metribuzin removal, with only a loss of sorptive capacity compared to pure bonechar observed. Keywords: Environmental remediation. Herbicide. Natural polymer. Carbonaceous material. Behavior.